Missions from Korea 2018: Mission Education - Mun, Sang cheol (International bulletin of mission research, 2018)
The Korean missionary movement keeps growing, but its rate of growth has declined. Korean missionaries are working in 159 countries through 159 mission agencies. At the end of 2017 the total number of Korean missionaries was 21,220, a yearly increase of only 145. There are more concerns, however, about qualitative maturation than about quantitative growth in the Korean missions circle. To facilitate maturation, efforts are needed to apply and integrate educational expertise. Domestic ministerial needs point to the strategic integration of missiology and education, and also to that of formal, nonformal, and informal educational aspects in mission education.